Human trafficking in the Qur'an: An Analysis of Sheikh Nawawi al-Bantani's Interpretation in Tafsir Marah Labid - Yusi Fadhilah Ananda; Ida Kurnia Shofa; Khoirun Nidhom (JIA (Jurnal Ilmu Agama), 2025)
Human trafficking is a form of modern slavery, involving the recruitment, transportation, transfer, harboring, or receipt of a person under the threat of violence, for the purpose of exploitation. The phenomenon of human trafficking, particularly of women and children, is not a new phenomenon that has emerged recently, but has existed since before the advent of Islam. In the Qur'an, human trafficking is not mentioned specifically, but there are several verses that indirectly or conceptually describe the practice of human trafficking. The verses of the Qur'an that describe this are QS. An-Nur: 33 and QS. Yusuf: 19-20. To explain these verses and delve deeper into human trafficking in the Qur'an, this study uses the book Tafsir Marah Labid by Sheikh Nawawi Al-Bantani. Based on this, the main issues in this paper are: how does Sheikh Nawawi Al-Bantani interpret QS. an-Nur: 33 and QS. Yusuf: 19-20, which address the issue of human trafficking, and how relevant it is? The objective of this study is to discuss human trafficking in the Tafsir Marah Labid by Syekh Nawawi Al-Bantani and how relevant his interpretation is to the issue of human trafficking in the present day. This research is a library research using the Tafsir Maudhu'i conseptual research method, based on Tafsir Marah Labid as the primary data source and other books and journals as secondary data sources. The data collection technique uses descriptive-analytical data analysis. The results of this research indicate that in QS. An-Nur: 33, Sheikh Nawawi strongly condemns the practice of forcing female slaves into prostitution, which is relevant to the contemporary phenomena of sexual exploitation and human trafficking. Meanwhile, in QS. Yusuf: 19–20, he highlights the sale of Prophet Yusuf as a concrete form of oppression and the commercialization of humans, which is highly contextual to modern human trafficking practices that treat humans as commodities.